Vinculin Regulates Assembly of Talin: β3 Integrin Complexes. Issue 6 (June 2014) - Nanda, Suman Yadav; Hoang, Thuy; Patel, Priya; Zhang, Hao
Abstract Vinculin is a talin‐binding protein that promotes integrin‐mediated cell adhesion, but the mechanisms are not understood. Because talin is a direct activator of integrins, we asked whether and how vinculin regulates the formation of integrin: talin complexes. We report that VD1 (aa 1‐258) and its talin‐binding mutant, VD1A50I, bind directly and equally to several β integrin cytoplasmic tails (βCT). Results from competition assays show that VD1, but not VD1A50I, inhibits the interaction of talin (Tn) and talin rod (TnR), but not talin head (TnH) with β3CT. The inhibition observed could be the result of VD1 binding to one or more of the 11 vinculin binding sites (VBSs) in the TnR domain. Our studies demonstrate that VD1 binding to amino acids 482‐911, a VBS rich region, in TnR perturbs the interaction of rod with β3CT. The integrin activation assays done using CHOA5 cells show that activated vinculin enhances αIIbβ3 integrin activation and that the effect is dependent on talin. The TnR domain however shows no integrin activation unlike TnH that shows enhanced integrin activation. The overall results indicate that activated vinculin promotes talin‐mediated integrin activation by binding to accessible VBSs in TnR and thus displacing the TnR from the β3 subunit. The study presented, defines a novel direct interaction of VD1 with β3CT and provides an attractive explanation for vinculin's ability to potentiate integrin‐mediated cell adhesion through directly binding to both TnR and the integrin cytoplasmic tail. J. Cell. Biochem. 115: 1206–1216, 2014. © 2013 Wiley Periodicals, Inc.